Body mass index, calcium supplementation and risk of colorectal adenomas. Issue 3 (30th October 2018) - Barry, Elizabeth L.; Lund, Jennifer L.; Westreich, Daniel; Mott, Leila A.; Ahnen, Dennis J.; Beck, Gerald J.; Bostick, Roberd M.; Bresalier, Robert S.; Burke, Carol A.; Church, Timothy R.; Rees, Judy R; Robertson, Douglas J.; et al.
Abstract : Calcium supplementation (1, 200 mg/day) did not significantly reduce colorectal adenomas in our recent randomized, controlled trial (Vitamin D/Calcium Polyp Prevention Study, VCPPS, 2004–2013) in contrast to our previous trial (Calcium Polyp Prevention Study, CPPS, 1988–1996). To reconcile these findings, we identified participant characteristics that differed between the study populations and modified the effect of calcium supplementation on adenomas or high‐risk findings (advanced or multiple adenomas). Compared to the CPPS, more participants in the VCPPS were obese (body mass index (BMI) ≥30 kg/m 2 ; 37.5% vs. 24.4%) and fewer had normal BMI (BMI <25 kg/m 2 ; 18.5% vs. 31%). BMI appeared to modify the effect of calcium supplementation on adenomas and especially on high risk‐findings: in the VCPPS, there was a 44% reduction in high‐risk findings among individuals whose BMI was normal (RR = 0.56, 95% CI = 0.26–1.23), but not among overweight (RR = 1.09, 95% CI = 0.62–1.91) or obese (RR = 1.54, 95% CI = 0.92–2.57) individuals ( p interaction = 0.03). Similarly, in the CPPS, there was a 56% reduction in high‐risk findings among individuals whose BMI was normal (RR = 0.44, 95% CI = 0.26–0.74), but not among overweight (RR = 0.87, 95% CI = 0.55–1.39) or obese (RR = 1.02, 95% CI = 0.57–1.82) individuals ( p interaction = 0.02). Standardization of each trial's findings to the BMI distribution in the other attenuated calcium's protective effect on adenomas in the CPPS but enhanced it in the VCPPS. In conclusion, 1, 200 mg/day calcium supplementation may reduce risk of colorectal adenomas among those with normal BMI but not in overweight or obese individuals; and differences in BMI distribution partially account for the apparent difference in calcium efficacy between the two trials. Abstract : What's new? Preclinical and observational evidence suggests that calcium supplementation exerts a protective effect against colorectal neoplasia. But in a recent randomized clinical trial, calcium supplementation was ineffective against colorectal adenomas, in contrast to a previous trial conducted by the same authors. Here, they found that body mass index (BMI) was higher among participants in the more recent trial, and that calcium supplementation was less effective among individuals with higher BMI. Differences in BMI distribution may partially account for the discrepancy between the two trials. Furthermore, 1200 mg/day calcium supplementation may only reduce risk of colorectal adenomas among individuals with normal BMI.